Gated Spillway Hydraulic Modelling Of Sultan Abu Bakar (SAB) Dam And The Gated Spillway - Isa, Azyrul Haffiz Mat (Universiti Sains Malaysia, 2017)
This study attempts to model the flow characteristic in a spillway physical model by using flow meter equipment. The experimental procedures include the data collection using a flow meter in laboratory. This experiment have seven cases for three types of opening gate. Type one is when only one radial gate is opened with three different cases for this type. First, second and third case refers to experiments with only radial Gate1, 2 and 3 opened respectively. The second type refers to a combination of two opened radial gate also with three different cases. For the first case in second type, only radial gate, Gate 1 and Gate 2 is opened. The second case in second type is when radial gate, Gate 1 and Gate 3 is opened and lastly, radial gate, Gate 2 and Gate 3 is opened. The third type for this experiment is combination of all 3 gates open. The flow meter output is discharge in (L/s). The error for this cases is not exceed 10% for all cases in this experiment. This is a good output to determine the problem in the SAB dam for the future. Moreover, the coefficient of determination,correlation coefficient (R2)values obtained from the experiment ranges from 0.96 to 0.99. Thus from the study, it can be concluded that the data obtained from the physical model of the Sultan Abu Bakar dam can be used to solve the problem and to know the cause from the physical model.